Collaborations in architecture and engineering - Olsen, Clare; Mac Namara, Sinéad Caitríona, 1977-. (New York Routledge, 2022)
This new edition of Collaborations in Architecture and Engineering explores how to effectively develop creative collaborations among architects and engineers. The authors, an architect and an engineer, share insights gained from their experiences and research on fostering productive communication, engaging in interdisciplinary discussions, and establishing common design goals. Together, they share the tools, methods, and best practices deployed by prominent innovative architects and engineers to provide readers with the key elements for success in interdisciplinary design collaborations. The book offers engaging stories about prominent architect and engineer collaborations--such as those between SANAA and Sasaki and Partners, Adjaye Associates and Silman, Grafton Architects and AKT II, Studio Gang and Arup, Foster + Partners and Buro Happold, Steven Holl Architects and Guy Nordenson and Associates, and among the engineers and architects at SOM. In the second edition, the newly added case studies showcase extraordinary buildings across the globe at a range of scales and typologies, tracing the facets of high-quality collaborations. Through the examples of these remarkable synergies, readers gain insights into innovative design processes that address complex challenges in the built environment. The second edition of Collaborations in Architecture and Engineering is a terrific sourcebook for students, educators and professionals interested in integrative design practice among the disciplines".
Introduction: Call for collaboration and diverse voices -- Architects and engineers in the academy: the challenge of the silos -- Architects and engineers in the profession: the barriers and benefits of collaboration -- Case studies in collaboration: Civic buildings -- Case studies in collaboration: Institutional buildings -- Case studies in collaboration: Transportation buildings.
Includes bibliographical references and index.
Keywords: Garden lighting; Architectural practice